(untitled) (Research, Society and Development, 2023)
Toothpastes are well-studied formulations, found in the form of a cream/paste or gel for cleaning teeth. Recently, dental tablets have been launched in the oral hygiene products market to be used in brushing, to replace traditional toothpastes. The aim of this study was to carry out a narrative review of the literature on dental tabs and identify the products available for online purchases in Brazilian stores, qualitatively analyzing the information provided by the producers. Two authors performed independent searches, with the terms ’tooth tabs’ and ’dental tablets’, in the shopping tab of the Google and Amazon Brazil platforms, from July 25 to August 1, 2022. For literature review, a search was performed in the Medline/PubMed and Embase databases, with the keywords “toothpaste”, “dental tablet”. The time cut performed was from 2000 to 2022. Ten products were found with prices between R0.25-R3.00 per unit of the tablet. As for the composition, only two of them contained fluoride salts. In the description of the stores/producers, aspects such as sustainability, practicality and the classification as ’vegan’ or ’natural’ were highlighted. In the literature search, only two articles were found on toothbrushing tablets (no clinical studies). Although toothpastes are available to consumers for purchase online, the cost of these products is considerably higher and more studies are needed before the dentist can prescribe them as an alternative to cream/paste or gel toothpastes.